The Impact of Positive Emotions of Purchasing Mediated Sales Promotion for Lifestyle and Hedonic Shopping Motivation - Kuncoro, Amin; Samekto, Agus AJi; Astuti, Widji - (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2023)
The aim of this research is to examine and analyze sales mediation promotions on the effect of lifestyle and hedonic shopping motivation on positive emotions. The research design uses a quantitative descriptive research with causality. The population and sample are students who use online purchasing applications in the City of Kudus, totaling 248 respondents. The results of the study explain that promotion mediates sales on the influence of lifestyle and hedonic shopping motivation. Because the role of sales promotion thereby increasing positive emotions. This proves that in essence sales promotion, especially sales using online applications, is able to foster hedonic shopping motivation.